Intentions to reciprocate vendor gifts amongst Malaysian purchasing executives - Wafa, Syed Azizi; Jantan, Muhamad; Chow, Jennifer Kim Eng (Universiti Utara Malaysia, 1999)
Business gift giving is a universal standard of conduct for most business oorganizations and industries (Beltramini 1992; Brenner and Molander 1977). Organizations use gift as means to show appreciation for past business and to influence the attitudes and behaviours of select, prestigious group of buyers in anticipation of future business (Meredith and Fried, 1977). Vendor gifts may serve as effective means of influencing customers or prospects. This research studied the effect of types of gift (personal or corporate gifts), cost of gift (expensive or inexpensive), and buyer-vendor relationship status (no relationship, moderate or strong) in relation to the buyers' (purchasing executives') feelings of indebtedness, perceived manipulations and intentions to reciprocate vendor's gifts.